Dynamic FDG-PET imaging for differentiating metastatic from non-metastatic lymph nodes of lung cancer - Wumener, Xieraili; Zhang, Yarong; Wang, Zhenguo; Zhang, Maoqun; Zang, Zihan; Huang, Bin; Liu, Ming; Huang, Shengyun; Huang, Yong; Wang, Peng; Liang, Ying; Sun, Tao (Frontiers in Oncology, 2022)
Objectives: 18F-fluorodeoxyglucose (FDG) PET/CT has been widely used in tumor diagnosis, staging, and response evaluation. To determine an optimal therapeutic strategy for lung cancer patients, accurate staging is essential. Semi-quantitative standardized uptake value (SUV) is known to be affected by multiple factors and may fail to differentiate between benign and malignant lesions. Lymph nodes (LNs) in the mediastinal and pulmonary hilar regions with high FDG uptake (SUVmax >2.5) due to granulomatous lesions such as tuberculosis, which has a high prevalence in China, pose a diagnostic challenge. This study aims to evaluate the diagnostic value of the quantitative metabolic parameters derived from dynamic 18F-FDG PET/CT in differentiating metastatic and non-metastatic LNs in lung cancer.